Zuhd and Mahabbah: Liberating Modern Society from Spiritual Desolation and Moral Decadence - Zaprulkhan, Zaprulkhan; Abas, Zainul; Sarif, Akbar (Department of Aqidah and Islamic Philosophy, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2025)
This paper discusses the significance of zuhd and maḥabbah in addressing the spiritual desolation and moral decadence of modern society. It explores the Sufistic approach to dealing with soul sickness, manifested in rising levels of spiritual anxiety and moral degradation. Zuhd functions as an internal mechanism for curbing negative impulses and immoral behaviors, while maḥabbah offers a counterbalance to materialism and self-centeredness by fostering love for others and for God. This literature-based study critically examines the Sufistic concepts as part of a social discourse on the spiritual emptiness and its effects on modern society. The study finds that a stronger emphasis on zuhd and maḥabbah can bring existential peace through ascetic practices, moral guidance, and community engagement. Islam is a holistic religion and a way of life, which loses its positive role in Muslim society if it does not support physical, moral, and spiritual restoration. This concern is especially urgent in an age where moral inversions—where right is perceived as wrong and wrong is right—have become increasingly normalized.